Optimal accuracy of unbiased Tullock contests with two heterogeneous players - Marco Sahm (Bamberg University, Bamberg Economic Research Group (BERG), 2022)
I characterize the optimal accuracy level r of an unbiased Tullock contest between two players with heterogeneous prize valuations. The designer maximizes the winning probability of the strong player or the winner's expected valuation by choosing a contest with an all-pay auction equilibrium (r ≥ 2). By contrast, if she aims at maximizing the expected aggregate effort or the winner's expected effort, she will choose a contest with a pure-strategy equilibrium, and the optimal accuracy level r < 2 decreases in the players' heterogeneity. Finally, a contest designer who faces a tradeoff between selection quality and minimum (maximum) effort will never (may) chose a contest with a semi-mixed equilibrium.
Keywords: C72; D72; 330; Tullock Contest; Heterogeneous Valuations; Accuracy; Discrimination; Optimal Design; All-Pay Auction